La reforma constitucional en materia político-electoral en México 2014 - Corona Nakamura, Luis Antonio (2015)
This essay presents a review of the background and main issues of the constitutional reform on the political-electoral matter, as published in the “Official Gazette” of the Federation on last February 10, 2014, the impact of which directly concerns the electoral institutions and the diverse juridical figures link to democracy.